Microbiological Assessment of Escherichia coli Contamination in Branded and Unbranded Soy Milk Sold at Bandungan Market, Semarang Regency, Indonesia - Nafisa Ailani; Slamet Isworo (School of Postgraduate Studies, Diponegoro Univer, 2026)
Soy milk is a plant-based beverage widely consumed as an alternative to cow's milk because of its nutritional value. However, inadequate hygiene and sanitation during production and handling may lead to Escherichia coli contamination, posing risks to food safety and public health. This study assessed the presence and contamination levels of E. coli in branded and unbranded soy milk sold at Bandungan Market, Semarang Regency, Indonesia. Thirty samples (15 branded and 15 unbranded) were purposively collected from five vendors and analyzed using the three stage Most Probable Number (MPN) method. Results were evaluated against the Indonesian National Standard (SNI 7388:2009), which sets a maximum limit of <3 MPN/mL for E. coli in beverages. Six samples (20.0%) were confirmed positive for E. coli, while 13 samples (43.3%) exceeded the regulatory limit. The Mann–Whitney U test showed no significant difference in contamination levels between branded and unbranded soy milk (U = 70.5, p = 0.3024), indicating comparable microbiological quality between the two product categories. These findings highlight microbiological contamination as a food safety concern affecting both product categories and underscore the need to strengthen hygiene practices, routine microbiological monitoring, and quality assurance throughout the production and distribution chain.